Identification of gingerenone A as a novel senolytic compound - Moaddel, Ruin; Rossi, Martina; Rodriguez, Stephanie; Munk, Rachel; Khadeer, Mohammed; Abdelmohsen, Kotb; Gorospe, Myriam; Ferrucci, Luigi (PloS one, 2022)
Senescent cells accumulate with aging and have been shown to contribute to age-associated diseases and organ dysfunction. Eliminating senescent cells with senolytic drugs has been shown to improve age phenotypes in mouse models and there is some initial evidence that it may improve the health of persons with chronic diseases. In this study, we employed WI-38 human fibroblasts rendered senescent by exposure to ionizing radiation (IR) to screen several plant extracts for their potential senolytic and/or senomorphic activity. Of these, ginger extract ( Zingiber officinale Rosc .) selectively caused the death of senescent cells without affecting proliferating cells. Among the major individual components of ginger extract, gingerenone A and 6-shogaol showed promising senolytic properties, with gingerenone A selectively eliminating senescent cells. Similar to the senolytic cocktail dasatinib and quercetin (D+Q), gingerenone A and 6-shogaol elicited an apoptotic program. Additionally, both D+Q and gingerenone A had a pronounced effect on suppressing the senescence-associated secretory phenotype (SASP). Gingerenone A selectively promotes the death of senescent cells with no effect on non-senescent cells and these characteristics strongly support the idea that this natural compound may have therapeutic benefit in diseases characterized by senescent cell accumulation.